Computationally Secure Quantum Oblivious Transfer. Issue 1 (19th November 2021) - Wang, Ping; Zhang, Rui; Jiang, Guohao; Sun, Zhiwei
Abstract: Oblivious transfer (OT) is one of the cornerstones of secure multiparty computation. It is clear that unconditionally secure OT is impossible. Any protocol for OT requires computational assumptions, such as number‐theoretic cryptographic assumptions or the assumptions of existence of one‐way functions. On the other hand, it is broadly believed that one‐way functions alone do not promise secure OT. However, in this paper, a novel computationally secure quantum oblivious transfer (QOT) protocol is proposed with the help of quantum channels under the minimum assumption requirements: the existence of one‐way functions. Abstract : Oblivious transfer (OT) is one of the cornerstones of secure multiparty computation. Any protocol for OT requires computational assumptions, such as number‐theoretic cryptographic assumptions or the assumptions of existence of one‐way functions. A novel computationally secure quantum oblivious transfer (QOT) protocol is designed with the help of quantum channels under the minimum assumption requirements: the existence of one‐way functions.